Time-optimal control of linear fractional systems with variable coefficients - Matychyn, Ivan; Onyshchenko, Viktoriia (Zielona Góra: Uniwersytet Zielonogórski)
Linear systems described by fractional differential equations (FDEs) with variable coefficients involving Reimann-Liouville and Caputo derivatives are examined in the paper. For these systems, a solution of the initial-value problem is derived in terms of the generalized Peano-Baker series and a time-optimal control problem is formulated. The optimal control problem is treated from the convex-analytical viewpoint. Necessary and sufficient conditions for time-optimal control similar to that of Pontryagin`s maximum principle are obtained. Theoretical results are supported by examples.
Keywords: fractional calculus; Riemann-Liouville derivative; variable coefficients; optimal control